PENYUSUNAN LAPORAN KEUANGAN UMKM BERBASIS SAK EMKM - Dabella Yunia; Galih Fajar Muttaqin; Windu Mulyasari; Kurniasih Dwi Astuti; Nana Nofianti; Tri Wahyudi; Muhammad Nawawi; Chandra Prasadhita (Jurnal Warta Desa (JWD), 2021)
The preparation of financial reports which has been seen as a difficult thing for Micro, Small and Medium Enterprises (MSMEs). The proposed community service program is a community service program that aims to provide easy solutions for Micro, Small, and Medium Enterprises in Banten Province in preparing financial reports. As a form of community service, community service was held with the theme "Workshop on the Preparation of MSME Financial Reports based on SAK EMKM". The workshop will be conducted in the form of presentation of basic accounting material and presentation of SAK EMKM.